On the fatigue damage micromechanisms in Si-solution–strengthened spheroidal graphite cast iron - Sujakhu, Surendra (2017)
Graphite nodules in Spheroidal graphite cast iron (SGI) play a vital role in fatigue crack initiation and propagation. The graphite nodule growth morphology can go through transitions to form degenerated graphite nodules other than spheroidal graphite nodules in SGI microstructure. These graphite nodules significantly influence damage micromechanisms on SGI and could act differently. Most of the damage mechanism studies on SGI were focused on the role of spheroidal graphite nodules on the stable crack propagation region. The roles of degenerated graphite nodules on SGI damage mechanisms were not frequently studied. In this work, fatigue crack initiation and propagation tests were conducted on EN-GJS-500-14 and observed under SEM to understand damage mechanisms of different graphite forms. Crack initiation tests showed dominant influence of degenerated graphite nodules where early cracks initiated in the microstructure. Most of the spheroidal graphite nodules were unaffected at the early crack initiation stage; some of them showed decohesion from the ferrite matrix and internal cracking. At the crack propagation region, graphite-ferrite matrix decohesion was the frequent damage mechanism observed with noticeable crack branching around graphite nodules and the crack passing through degenerated graphite nodules. Finally, graphite nodules after decohesion acted like voids which grew and coalesced to form microcracks eventually causing rapid fracture of the remaining section.